Exploring the link between work and health: Workaholism and family history of metabolic diseases. Issue 2 (3rd April 2017) - Aziz, Shahnaz; Wuensch, Karl; Shaikh, Saame Raza
Abstract : Purpose: The purpose of this paper is to examine if facets of workaholism are associated with a family history of metabolic diseases. Design/methodology/approach: Data on workaholism and family history of health issues were collected, through administration of an online survey, from 194 employees. Findings: Workaholism significantly related to a family history of metabolic diseases. Research limitations/implications: Future researchers should collect objective disease data, examine work-related moderators as well as potential mediators, and implement longitudinal designs with much larger samples. That said, the data reveal a correlation between workaholism and family history of metabolic disease. Practical implications: The results provide valuable information to help promote a healthy workforce and to improve employees' health by reducing workaholic tendencies. They could also help to minimize health-related costs associated with metabolic diseases that could develop in parallel with workaholism, as well as costs in terms of a loss in productivity due absenteeism. Originality/value: It is, the authors believe, the first study to investigate the relationship between facets of workaholism and family history of health issues that have often been associated with metabolic diseases.